Effects of mountaintop mining on fish distributions in central Appalachia. Issue 4 (28th April 2013) - Hopkins, Robert L.; Roush, Jordan C.
Abstract: Mountaintop mining with valley fills (MTM/VF) is the main source of landscape change in central Appalachia. While our knowledge of the local‐scale effects of MTM/VF on stream chemistry and biotic assemblages has recently improved, the effects at the landscape scale are less well known. In this study, we explore the effects of MTM/VF on the distributions of six fish species with contrasting ecologies in the upper Kentucky River basin, an area heavily affected by MTM/VF. Using a museum‐based data set of 239 occurrence records, land use/land cover data and boosted regression tree modelling, we were able to create robust predictive models for the focal species (AUCs = 0.82–0.93). Models explained from 41.2 to 71.9% of the variation in species distributions. We detected a marked negative influence of MTM/VF in four of the six species distribution models – with relative influences ranging from 5.9–12.7%. Species typically inhabiting faster‐flowing riffle and run mesohabitats appeared to respond more strongly to MTM/VF. Interestingly, the mean patch size of MTM/VF was more influential than the overall proportion of the watershed affected by MTM/VF in our models. Thus, our data suggest the spatial pattern of mining disturbance is very important in determining the cumulative impact of MTM/VF. Considering the central Appalachian region is a continental hot spot for freshwater biodiversity, establishing a firm understanding of the effects of MTM/VF at the landscape scale is essential if we wish to protect these natural resources.